Double review of the right colon vs single review during colonoscopy for the detection of colon polyps and adenomas: systematic review of the literature - Daza Castro, Erlison Mauricio (2023)
Colonoscopy screening is an effective method to prevent colon cancer through the detection of polyps on which colon cancer develops in a higher percentage; however, the detection of these lesions varies in the different segments of the colon and the detection rate of them in the right colon is usually lower. Objective: The objective of this study is to evaluate whether double endoscopic revision of the right colon during colonoscopy is a mechanism to improve its performance in terms of polyp detection rate (TDP) and adenoma detection rate (ADR). Materials and methods: Systematic review and meta-analysis of the literature including randomized clinical trials that evaluated repeat right-sight examination by colonoscopy compared to standard view to improve detection of polyps and adenomas. The protocol for this decision was published in PROSPERO under the code CRD42022356509. Results: Five studies involving 2729 participants were included. Polyp detection was reported in 585/1197 patients (48.87%) after the second review, compared with 537/1206 (44.52%) of patients who received a single examination (p< 0.05), for a combined RR of 1.09 (95% CI: 0.97-1.23) (I2 was 44%). Detection of adenomas was reported in 830/1513 patients (54.75%) after the second review, compared with 779/1509 (51.62%) of patients who received a single examination (p < 0.05), for a combined RR of 1.06 (95% CI: 1.00-1.13) (I2 was 0%). Conclusion: Second examination of the right colon by colonoscopy may have a modest improvement in the detection of polyps and adenomas.